Glacial melt content of water use in the tropical Andes. (2nd November 2017) - Buytaert, Wouter; Moulds, Simon; Acosta, Luis; De Bièvre, Bert; Olmos, Carlos; Villacis, Marcos; Tovar, Carolina; Verbist, Koen M J
Abstract: Accelerated melting of glaciers is expected to have a negative effect on the water resources of mountain regions and their adjacent lowlands, with tropical mountain regions being among the most vulnerable. In order to quantify those impacts, it is necessary to understand the changing dynamics of glacial melting, but also to map how glacial meltwater contributes to current and future water use, which often occurs at considerable distance downstream of the terminus of the glacier. While the dynamics of tropical glacial melt are increasingly well understood and documented, major uncertainty remains on how the contribution of tropical glacial meltwater propagates through the hydrological system, and hence how it contributes to various types of human water use in downstream regions. Therefore, in this paper we present a detailed regional mapping of current water demand in regions downstream of the major tropical glaciers. We combine these maps with a regional water balance model to determine the dominant spatiotemporal patterns of the contribution of glacial meltwater to human water use at an unprecedented scale and resolution. We find that the number of users relying continuously on water resources with a high (>25%) long-term average contribution from glacial melt is low (391 000 domestic users, 398 km 2 of irrigated land, and 11 MW of hydropower production), but this reliance increases sharply during drought conditions (up to 3.92 million domestic users, 2096 km 2 of irrigated land, and 732 MW of hydropower production in the driest month of a drought year). A large proportion of domestic and agricultural users are located in rural regions where climate adaptation capacity tends to be low. Therefore, we suggest that adaptation strategies should focus on increasing the natural and artificial water storage and regulation capacity to bridge dry periods.